A prospective study of calorimetric estimation of blood loss in TURP cases - Kirde, Dattatraya; Thorat, Santosh; Mishra, Shivayak; Dube, V S (Surgical Review: International Journal of Surgery, Trauma and Orthopedics, 2016)
Introduction: BEP is hyperplasia of prostatic stromal epithelial cells to form discreate nodules in transitional zone of prostate. It leads to constriction of urethral opening which gives rise to associated lower urinary tract symptoms such as frequency, urgency, nocturia. Initially disease can be managed by drug treatment but eventually most of the patients require surgical management. TURP remains gold standard treatment. Blood loss during and after procedure is major problem. This study was planned to evaluate the approximate blood loss with the help of simple technique of colorimatry. Method: This study is carried out on 50 patients with BEP who underwent TURP in our institute from October 2014 and June 2015. Irrigation fluid collected during TURP, post operative day 1 & 2 subjected to calorimetric estimation of blood loss using Drabkin’s reagent. Results: The results were suggestive of approximate average blood loss during TURP procedure as 267 ml, post operative day 1 blood loss 98.9ml and post operative day 2 loss was 58.1ml. However the average blood loss changes according to the size of prostate and duration of the procedure. Conclusion: calorimetric estimation of blood loss during and post operative period is an easy, economically feasible, quick method to guide the management of blood requirement for the patient. This can be useful in patients with BEP and bleeding diathesis.